To save a Life [Motion Picture] - Baugh, Brian (Washington : New Song Pictures, 2010)
Jake Taylor has everything. He has a beautiful girl, he's the champion in basketball and beer pong, and everyone loves him. Then, an old childhood friend, whom Jake used to be friends with, commits suicide. Jake begins to think. He wonders what he could've done to save his friend's life. A youth minister tells him that Jake needs God. So Jake becomes a Christian. However, things begin to spin out of control. His dad is cheating on his mom, his girlfriend is pregnant, and his former friends ridicule and mock him. During all this, Jake is going to realize just what it means to be a Christian and how, to save a life
Rated PG-13 for mature thematic elements involving teen suicide, teen drinking, some drug content, disturbing images and sexuality
Keywords: Christian life